2021
DOI: 10.1021/acs.nanolett.1c03169
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Low Power and Ultrafast Memristor on p-Type van der Waals SnS

Abstract: Memristor devices that exhibit high integration density, fast speed, and low power consumption are candidates for neuromorphic devices. Here, we demonstrate a filament-based memristor using p-type SnS as the resistive switching material, exhibiting superlative metrics such as a switching voltage ∼0.2 V, a switching speed faster than 1.5 ns, high endurance switching cycles, and an ultralarge on/off ratio of 10 8 . The device exhibits a power consumption as low as ∼100 fJ per switch. Chip-level simulations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 35 publications
1
67
0
Order By: Relevance
“…In simulation, the top‐level architecture includes tiles, global buffers, neural function peripherals, and weight gradient calculation functions. [ 38 ] The tile also contains multiple processing elements (PEs), which can be further divided into Transpose Synaptic Arrays, and can support training in the NeuroSim core, as shown in Figure 7c. In the readout mode of the BTO−CeO 2 ‐based array simulation, we adopt parallel readout, the structure of which is shown in Figure 7d.…”
Section: Resultsmentioning
confidence: 99%
“…In simulation, the top‐level architecture includes tiles, global buffers, neural function peripherals, and weight gradient calculation functions. [ 38 ] The tile also contains multiple processing elements (PEs), which can be further divided into Transpose Synaptic Arrays, and can support training in the NeuroSim core, as shown in Figure 7c. In the readout mode of the BTO−CeO 2 ‐based array simulation, we adopt parallel readout, the structure of which is shown in Figure 7d.…”
Section: Resultsmentioning
confidence: 99%
“…Lu et al reported Ag/SnS/Pt memristor devices that allow for robust facile Ag filament formation attributed to the presence of Sn vacancies (Fig. 4i) [140]. In contrast to most TMCs, which are intrinsically n-type due to chalcogen vacancies, SnS is an intrinsically p-type semiconductor due to Sn vacancies [145].…”
Section: Memristor-based Neuromorphic Computing Applicationsmentioning
confidence: 99%
“…The measured current is ≈100 pA at the read voltage of 0.01 V. Accordingly, the energy consumption for the fabricated memristor is ≈100 fJ per switch, suggesting low power applications from our BiOI memristive device. [ 34,38 ]…”
Section: Resultsmentioning
confidence: 99%
“…The measured current is ≈100 pA at the read voltage of 0.01 V. Accordingly, the energy consumption for the fabricated memristor is ≈100 fJ per switch, suggesting low power applications from our BiOI memristive device. [34,38] In order to further understand the conduction mechanism of the memristor, the positive part of the I-V curve in Figure 2b is re-plotted in double logarithmic scales (Figure 2c). For the LRS, the fitted slope is 1.030, suggesting the ohmic conduction mechanism.…”
Section: Resultsmentioning
confidence: 99%